On q-Convex Functions Defined by the q-Ruscheweyh Derivative Operator in Conic Regions - Mehwish Jabeen; Sarfraz Nawaz Malik; Shahid Mahmood; S. M. Jawwad Riaz; Md. Shajib Ali (Journal of Mathematics)
The core objective of this article is to introduce and investigate a new class β−UCVqλA,B of convex functions associated with the conic domain defined by the Ruscheweyh q-differential operator. Many interesting properties such as sufficiency criteria, coefficient bounds, partial sums, and radius of convexity of order α for the functions of the said class are investigated here.